Analisis Finansial dan Sensitivitas Usaha Kecil Menengah Dodol Coklat - Fibra Nurainy; Otik Nawansih; Merry Monika Sitanggang (Jurnal Penelitian Pertanian Terapan, 2015)
This research was purposed to determine financial aspects of chocolate dodol home industry. The result of investment feasibility are reasonable to continue (NPV>0, Net B/C >1,IRR> 22% discount rate and raw’s material (cocoa beans) as many as 10%-50% and the fuel as many as 15%-90 PP< 5 years of economical’s age. The result of sensitivity variable cost increase likes % still reasonable to continue (NPV>0, Net B/C >1,IRR> 22% discount rate and PP< 5 years of economical’s age). Keywords: Chocolate dodol, Financial Analysis, Sensitivity.